2014
DOI: 10.1021/je500369e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paraffinic Group on Interfacial Tension Behavior of CO2–Asphaltenic Crude Oil Systems

Abstract: The interfacial tension (IFT) of a crude oil/CO 2 system is recognized as the main property affecting the efficiency of CO 2 flooding during an enhanced oil recovery (EOR) process. The addition of a paraffin group hydrocarbon to asphaltenic crude oils as an asphaltene precipitant component is aimed to mimic the asphaltene precipitation process during crude oil production and transportation. Asphaltene precipitation would critically affect the interfacial behavior of crude oil/CO 2 systems. In the first part of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…For example, the CH 4 -dominated HCs pre-saturated live light oil-CO 2 system was found to have a higher IFT/MMP, whereas the intermediate HCs pre-saturated one has a lower IFT/MMP in comparison with that of the dead light oil-CO 2 system. 18 Similar results were also found in terms of the effect of injection gas composition on the IFT/MMP studies. 15 Moreover, the effect of feed ratio of injection gas to oil on the measured IFT/MMP cannot be ignored although there is no general consensus on it.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, the CH 4 -dominated HCs pre-saturated live light oil-CO 2 system was found to have a higher IFT/MMP, whereas the intermediate HCs pre-saturated one has a lower IFT/MMP in comparison with that of the dead light oil-CO 2 system. 18 Similar results were also found in terms of the effect of injection gas composition on the IFT/MMP studies. 15 Moreover, the effect of feed ratio of injection gas to oil on the measured IFT/MMP cannot be ignored although there is no general consensus on it.…”
Section: Introductionsupporting
confidence: 74%
“…This is because the addition of CH 4 -dominated produced gas into oil sample reduces the CO 2 solubility in the oil phase. 18 Two respective MMPs are determined to be 11.6 and 26.5 MPa from the DIM at T ¼ 53.0 and 116.1 C, both of which are slightly lower than 13.7 and 29.7 MPa of the Pembina live oil-pure CO 2 system at the same temperature. The effects of initial oil composition on the determined MMPs are further summarized in Fig.…”
Section: Temperature Effectmentioning
confidence: 87%
“…Solubility of components of the crude oil in CO 2 is crucial to the recovery rate. It has been found that light alkanes (C 3-10 ) compared with heavier alkanes were recovered faster and more from the crude oil phase because of their better solubility in CO 2 (Cao & Gu, 2013;Rudyk, Spirov, & Sogaard, 2013); in addition, IFT between light alkanes and CO 2 are lower than those between the heavy alkanes and CO 2 (Mahdavi, Zebarjad, Taghikhani, & Ayatollahi, 2014a). In the extraction fields, a high extraction rate of a compound largely depends on its good solubility in CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Luo, Zhang, Wang, and Huang (2012), solubility of n-hexane in CO 2 is as high as 6.18 mol % at 328 K, 8.95 MPa. Using a mixed solvent (CO 2 with alkanes, light petroleum, or alcohols) instead of pure CO 2 is a common way to increase the solubility (Catchpole, Grey, & Noermark, 1998;Mahdavi, Zebarjad, Taghikhani, & Ayatollahi, 2014b;Zolghadr, Escrochi, & Ayatollahi, 2013). De Lucas, Gracia, Rincon, and García (2007) studied the solubility of squalene, orange roughy, spiny dogfish, and cod liver oil in scCO 2 , finding that the solubility was obviously improved by the addition of ethanol, 7.75% of ethanol resulted in an improvement in the solubility of cod liver oil from 4.81 to 9.07 g kg −1 at 333 K, 20 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Ethoxylated fatty acid methyl esters are new biodegradable surfactants that easily hydrolyze to nontoxic and non-surface active components in sewage systems [24][25][26][27]. Compared to ethoxylated alcohols, they have better properties, lower aquatic toxicity and higher biodegradability [27,28].…”
Section: Introductionmentioning
confidence: 99%